ISU KESEHATAN DALAM SENGKETA IMPOR DAGING AYAM ANTARA INDONESIA-BRAZIL DI WTO - Siswanto, Ari (Arena Hukum, 2021)
AbstractThis paper discusses the issue of human health protection as one of the exceptions of GATT obligations, considering the elements in Article XX (b) of GATT are still general in nature and thus have the potential to bring different interpretation. Focusing on the elements of "necessary to protect human life or health" and "arbitrary or unjustifiable discrimination", this paper seeks to explore the various meanings of Article XX (b) GATT, including its implementation in an in concreto dispute, namely Indonesia's dispute with Brazil over chicken meat import policy. The result shows that the element of "necessary to protect human life or health" will be deemed if the state can demonstrate the existence of health risks, adopt necessary policies that mitigate such risks, and there is no other policy alternative more friendly to international trade available. In relation to the more subjective element of "arbitrary or unjustifiable discrimination", the principle of good faith has not yet given a place in the consideration of this element.AbstrakTulisan ini membahas isu perlindungan kesehatan manusia sebagai salah satu pengecualian dari kewajiban-kewajiban GATT, mengingat bahwa unsur-unsur dalam Artikel XX(b) GATT masih bersifat umum dan berpeluang memunculkan perbedaan penafsiran. Berfokus pada unsur â€œnecessary to protect human life or healthâ€ dan â€œarbitrary or unjustifiable discriminationâ€, tulisan ini menelusuri berbagai pemaknaan terhadap Artikel XX(b) GATT, termasuk implementasinya dalam sengketa in concreto, yakni sengketa Indonesia melawan Brazil terkait kebijakan impor daging ayam. Hasilnya, unsur â€œnecessary to protect human life or healthâ€ dianggap terpenuhi kalau negara itu bisa menunjukkan keberadaan risiko kesehatan, mengambil kebijakan yang mampu mengurangi risiko tersebut dan memang harus diambil, serta tidak tersedia alternatif kebijakan lain yang lebih ramah terhadap perdagangan internasional. Terkait unsur â€œarbitrary or unjustifiable discriminationâ€ yang lebih subjektif, terungkap prinsip itikad baik belum mendapat tempat di dalam pertimbangan atas unsur ini.